Diffeomorphism-equivariant configuration spaces with twisted partial summable labels - Yon, H (2017)
We construct the configuration space of points in a smooth manifold with twisted noncommutative partial summable labels. The theory of twisted operads is developed to encode twisted noncommutative summations. We also define a diffeomorphism-equivariant scanning map from the configuration space to a section space and show that it is a weak equivalence. To achieve the equivariance the configuration space is mapped to a section space over the space of all disks in the ambient manifold.